A CRUSTAL-SCALE, OROGEN-PARALLEL STRIKE-SLIP FAULT IN THE MIDDLE URALS: AGE, MAGNITUDE OF DISPLACEMENT, AND GEODYNAMIC SIGNIFICANCE - Hetzel R.; Glodny J. (My University, 2002)
The kinematic evolution of an orogen-parallel strike-slip fault in the Middle Urals demonstrates that orogen-parallel mass transfer was an important, previously underestimated process during the syncollisional evolution of the Middle Urals. The Kyshtym strike-slip fault extends NNE, parallel and adjacent to the Main Uralian fault, which is the main suture of the Uralide orogen. The Kyshtym fault is interpreted as one of two conjugate strike-slip fault zones that have accomodated the longitudinal transfer of material along the margins of a rigid indenter belonging to the East European craton. The dextral Kyshtym shear zone was active under retrograde lower amphibolite to middle/lower greenschist facies conditions. Four metagranitic, muscovite-bearing mylonites yielded Rb–Sr internal mineral isochron ages of 247.5±2.9, 244.5±6.5, 240.0±1.4, and 240.4±2.3 Ma, whereas a biotite-rich sample, without muscovite, gave a mineral isochron age of 229.1±3.2 Ma. The results indicate almost complete Sr-isotopic reequilibration on the hand specimen scale during mylonitization. The muscovite ages are interpreted as deformation ages and demonstrate a Late Permian/Early Triassic age for the Kyshtym shear zone. The shear zone transects a pre-orogenic syenite intrusion of Ordovician age. A maximum shear strain of γ=7±3 is estimated from the shape of the ductily deformed syenite body in map view and from the length/width ratios of deformed amphibolite bodies in the country rock. This shear strain suggests a maximum displacement of 28±12 km for the ~4-km-thick Kyshtym shear zone. A younger brittle fault, oriented subparallel to the shear zone, accomplished an additional horizontal displacement of 15±3 km; thus, the total displacement along the fault system is 43±15 km.